THE CONCEPT AND THE STRUCTURE OF THE INTERNATIONAL SPACE LAW (METHODOLOGICAL ASPECT) - Bezzubov, Dmytro O. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
Purpose: the article discusses the development of the theorist foundations of space law. The views of scientists on the problem of the principles of space law are analyzed. The list of normative acts in this area is determined. Methods: classification of international instruments in the field of space law. The ways of further development of international and domestic space law as a sphere of activity of humanity are determined. Discussion: there is a conclusion about the necessity of development of domestic space law.